The use of chiral auxiliaries in the synthesis of chemically and biologically important chiral compunds - Bixa, Thobela Lukas (Department of Chemistry, 2014)
Chiral synthons of chemical and biological importance have been synthesised using imidazolidinone and Evans' oxazolidinone chiral auxiliaries (CA). The thesis comprises two parts, which were carried out at the Universities of Cape Town, RSA and University of Michigan in the USA. In part 1, carried out in the Chemistry Department of the University of Cape Town, an imidazolidinone-CA was utilised in developing a malonate-based methodology to synthesise compounds containing a quaternary stereogenic centre (QSC). With this methodology, a small library of malonate-based QSC-containing synthons has been synthesised in both high yields (> 87 %) and high stereoselectivities (dr, ≥ 93 : 7 %). The CA was cleaved using an EtSLi SNAc reaction followed by a double reduction using the Fukuyama protocol followed by NaBH4 to afford α,α'-disubstituted-2-hydroxy synthons in 55-65% yield over two steps respectively. In part 2, carried out in the Chemistry Department at the University of Michigan, the macrolide core (10) of lactimidomycin was synthesised for biological evaluation over 11-linear steps in a 6.1 % overall yield. The synthesis exploited an Evans' oxazolidinonemediated aldol reaction to construct the Evans syn-adduct, a Suzuki cross-coupling for the (E,Z)-diene construction, and an intramolecular Horner-Wadsworth-Emmons olefination for construction of the E-enone of the macrolide.